1990
DOI: 10.1159/000107130
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Affective and Cognitive Symptoms: The Epidemiological Evidence

Abstract: Affective and cognitive symptoms co-occur considerably above chance in clinical (i.e. treated) samples. By contrast, in population-based surveys, the syndromes of depression and dementia do not occur at the case level more than by chance, but symptoms of each may correlate significantly though never strongly. Epidemiological data from prospective longitudinal studies are now sought, focussed on cases showing both groups of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…It should also be noted that, in accordance with other studies (Henderson, 1990;Wragg and Jeste, 1989), we found depressive features in about 40% of patients. However, it has been suggested that the use of self-rating depression scales in dementia may be of questionable reliability because of possible patient denial or lack of insight (Mahurin et al, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…It should also be noted that, in accordance with other studies (Henderson, 1990;Wragg and Jeste, 1989), we found depressive features in about 40% of patients. However, it has been suggested that the use of self-rating depression scales in dementia may be of questionable reliability because of possible patient denial or lack of insight (Mahurin et al, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…In clinical samples of dementia patients, a high prevalence of depression has been reported [2]. In general population Included only episodes of depression occurring before age 55.…”
Section: Introductionmentioning
confidence: 99%
“…Most of such information comes from clinic-based studies of treated series. The outcome variables have typically included the rate of recovery, the coexistence of depression with dementia and the progression of depression to dementia (Cole, 1990;Baldwin and Jolley, 1986;Baldwin, 1988;Gordon, 1981;Reding et al, 1985;Reifler et al, 1986;Henderson, 1990;Blazer et al, 1980;Post, 1972;Murphy, 1983;Burvill et al, 1989). However, clinic based studies have limitations.…”
mentioning
confidence: 99%